The effects of reflected glare and visual field lighting on computer vision syndrome. (25th February 2019) - Lin, Chao‐Wen; Yeh, Feng‐Ming; Wu, Bo‐Wen; Yang, Chang‐Hao
Abstract : Background: Computer vision syndrome is common and affects performance of visual tasks. Background illumination, light source, light compensation, position of the display, contrast and glare are environmental factors associated with computer vision syndrome. The aim of this study is to investigate the effects of reflected glare and visual field lighting on computer vision syndrome. Methods: In a reflected glare experiment, participants performed a two‐hour visual task using a glossy, matte, or glare‐free surface display in two visual environments (normal, glare). In a visual field lighting experiment, participants performed the visual task in dim lighting, uneven supplementary lighting, or uniform supplementary lighting. Visual function parameters, including critical fusion frequency, heterophoria, amplitude of accommodation and accommodative facility were evaluated by the investigators and a visual fatigue questionnaire was completed before and after the visual task. Visual performance was also recorded. In addition, the variation of pupil size under different lighting conditions was analysed. Results: Critical fusion frequency was the only visual function parameter which decreased significantly after the visual task. The questionnaire score was significantly higher in a glare environment and was lower when the task was performed using a glare‐free display. Visual performance was significantly worse in the glossy display group. The increment in the questionnaire score was smaller in the uniform supplementary lighting group. Visual performance was significantly worse in the dim lighting or uneven supplementary lighting group, but not in the uniform supplementary lighting group. Variation in pupil size was significantly greater in the dim lighting condition than in the supplementary lighting condition. Conclusion: Critical fusion frequency is an effective indicator of computer vision syndrome. Glare‐free displays could alleviate visual fatigue and preserve visual performance. Uniform supplementary lighting could decrease variation in pupil size and prevent eye strain.